Analysis of the need for academic guidance and counseling for guidance and counseling students at the University of Jambi - Affan Yusra; Rasimin Rasimin; Freddi Sarman (Proceeding of the International Conference on Global Education and Learning, 2024)
This research focuses on identifying and evaluating unmet academic counseling needs for guidance and counseling students at Jambi University. Academic counseling is crucial for supporting students' academic achievement and professional development. However, challenges such as ineffective communication with academic advisors, limited access to services, and low student awareness of counseling benefits can hinder learning and skill development. The study aims to explore specific unmet counseling needs and barriers to utilizing guidance services at the university. Using a qualitative approach with semi-structured interviews, the research is grounded in Trautwein and Bosse’s academic counseling theory and Knowles' theory of needs. Data analysis is conducted through thematic and narrative approaches. Findings show that, similar to studies on German students, individual and organizational counseling needs are prioritized over learning and social needs. This reflects concerns among Jambi University students about understanding their major, setting academic goals, comprehending the curriculum, and lack of preparation for academic challenges. The research ultimately provides recommendations to enhance the effectiveness of academic counseling services at the university.